Design of a New Carbon Paste Electrode Modified with TiO2 Nanoparticles to Use in an Electrochemical Study of Codeine and Simultaneous Determination of Codeine and Acetaminophen in Human Plasma Serum Samples. Issue 9 (22nd August 2014) - Mashhadizadeh, Mohammad Hossein; Rasouli, Fatemeh
Abstract A new electrochemical sensor was fabricated via TiO2 nanoparticles onto a carbon paste electrode. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) studied the response of the modified electrode toward codeine. The effects of pH, modifier amount, pulse amplitude, and scan rate of potential have been examined. Using DPV, we could measure simultaneously codeine and acetaminophen in one mixture. The detection limits of 0.018 and 0.050 µmol L−1 were achieved for codeine and acetaminophen, respectively. The electrooxidation pathway, transfer coefficient, and standard rate constant, are estimated. The proposed voltammetric sensor was successfully applied to determination of codeine and acetaminophen in human plasma serum samples.